From famine to food security: A new agenda and approach must be adopted - Fan, Shenggen; Olofinbiyi, Tolulope (Wiley, 2012)
From Famine to Food Security: A New Agenda and Approach Must be AdoptedThe occurrences of two global food crises in 3 years as well as the recent dire situation in the Horn of Africa, which have attracted much policy attention, are stark reminders that the risk of catastrophic food crises, or famine, remains large. With rapid population growth and changing demographics, growing natural resource constraints, high and volatile food prices, rising energy prices, biofuel expansion, and climate change, global food security has become more difficult to achieve. Research, policy and practice continue to seek solutions to transit famine to sustained food security in many part of the world. While this article does not provide an exhaustive discussion about the actions needed to prevent recurring food crises and famine, it recommends a broad set of actions that are urgently needed. The actions, which must be implemented through a coordinated effort of global, national and local actors, are: i) scale‐up emergency assistance and productive social safety nets; ii) improve agricultural productivity and promote technological innovations; iii) establish innovative institutional mechanisms; iv) support country‐led strategies, fill knowledge gaps, and build capacity; and v) improve governance and tackle conflicts. Swift implementation of these actions is needed to effectively prevent recurring food crises on a large scale.